2016
DOI: 10.5539/ijbm.v11n4p71
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium Tourist Enterprises and Social Media Adoption: Empirical Evidence from Tanzanian Tourism Sector

Abstract: The increasing competition and the highly demands of globalization in tourism sector are increasing challenges in the market and operation of Small and Medium enterprises in Tanzania. In order to cope with these challenges, it is evidenced that the adoption of social media networking is an enabler of small and medium tourist enterprises in quest of enhancing competitiveness in their globalized market place. Despite of this benefit offered by Social Media (SM) to SMEs, very little is known on the factors influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 13 publications
1
16
2
Order By: Relevance
“…Out of the three groups of factors, technological features are considered as the most important ones. Previous research studies in the field of SMA in the hospitality industry have mostly investigated and emphasized on the power of organizational features [43,45], while other studies have found out that the technological context has insignificant influence on SMA [21,44]. This study contributes to ongoing research on organizational SMA by indicating that technological features are the most important determinants, while the organizational and environmental context are less significant.…”
Section: Structural Modelmentioning
confidence: 60%
See 1 more Smart Citation
“…Out of the three groups of factors, technological features are considered as the most important ones. Previous research studies in the field of SMA in the hospitality industry have mostly investigated and emphasized on the power of organizational features [43,45], while other studies have found out that the technological context has insignificant influence on SMA [21,44]. This study contributes to ongoing research on organizational SMA by indicating that technological features are the most important determinants, while the organizational and environmental context are less significant.…”
Section: Structural Modelmentioning
confidence: 60%
“…TOE has recently been applied for the investigation of social media use by firms of the hospitality sector. Ndekwa and Katunzi [44] surveyed the factors influencing adoption of online social media among small and medium tourist enterprises in Tanzania and their findings revealed that organizational and environmental context are significantly influencing adoption of social media, while technology context was found to be insignificant factor. More recently, Matikiti et al [45] employed both Technology Acceptance Model (TAM) and TOE framework to identify factors that influence attitude towards the use of social media marketing by small tourism businesses (tour operators, travel agencies) in South Africa.…”
Section: The Technology-organization-environment (Toe) Frameworkmentioning
confidence: 99%
“…Most studies on social media adoption have focused on companies/organizations in relation to social media use in marketing, benefits of social media, and factors affecting adoption (Sinclaire and Vogus 2011, Mandal and McQueen 2012, Thackeray et al 2012, Durkin et al 2013, Nah and Saxton 2013, Dahnil et al 2014, Lorenzo-Romero et al 2014, Ainin et al 2015, Ndekwa and Katunzi 2016, Wood and Khan 2016, Abubakar et al 2017, Matikiti et al 2018. Fewer studies have looked at social media adoption on the consumer side.…”
Section: Social Media Adoptionmentioning
confidence: 99%
“…The results show that there is a significant effort of Greek food manufacturing firms to take advantage of the potential of social media. Ndekwa and Katunzi (2016) in their study aims at filling the gap by examining factors influencing adoption of Social Media Networking among SMEs in Tanzanian tourism sector. This study recommended that in order SMEs to continuously be competitive in this global and dynamic market they should continue to adopt the use of social media networking as a tool to capture more customers worldwide.…”
Section: Other Relevant Studies Related With Social Media and Smesmentioning
confidence: 99%